The Importance of a Nursing Theoretical Framework for Nursing Practice: Rogers’ Science of Unitary Human Beings and Barrett’s Theory of Knowing Participation in Change as Exemplars - Malinski, Violet (Cultura del cuidado, 2018)
Martha E. Rogers (1970, 1990, 1992) was one of the first to maintain that nursing is both a science and an art, a learned profession based on an organized body of nursing-specific knowledge. Indeed, as early as 1963, she wrote, “Instruction in the theoretical basis of nursing practice is the hard core of baccalaureate education in nursing…professional nursing services cannot be provided unless the theoretical base is present” (1963, p. 61). Rogers saw the unique focus of nursing as irreducible human beings and environment, both identified as energy fields, with the purpose of nursing as promoting well-being and health throughout the life process, including dying. Nurses help people participate knowingly in the life process, actualizing potentials deemed commensurate with personal wellbeing. Together, nurses and clients participate mutually and knowledgeably to optimize potentials. Building on these assumptions, Elizabeth E. A. M. Barrett (1988, 2010, 2015) derived her theory of power as knowing participation in change and a tool to measure it while working with Rogers as a student in the doctoral program at New York University. The author provides a brief overview of both Rogers’ Science of Unitary Human Beings and Barrett’s theory of power as knowing participation in change and discusses their relevance to practice.